3D CFD analysis of species transport and electrochemical behavior in a PEM electrolyzer - Safiye Nur Ozdemir (Case Studies in Thermal Engineering)
This investigation focuses on simulating a single-cell Proton Exchange Membrane Electrolyzer (PEMEL) in water electrolysis. This study utilizes a 3D (three-dimensional) multiphysics model to simulate the electrochemical processes and species transport occurring within the cell. A commercial computational fluid dynamics (CFD) code from the ANSYS package was employed to solve the computational model. The model validation is confirmed by comparing it with experimental data from existing literature. Different physical parameters examined in this investigation include temperature, membrane thickness, and porous transport layer (PTL) thickness. The results show that increasing temperature can improve PEMEL performance. When the temperature rises from 333.15 K to 353.15 K, the current density increases from 0.8252 A/cm2 to 1.0280 A/cm2 at a voltage of 1.65 V. For the influence of PTL thickness, the cell performance has deteriorated as the PTL's thickness increases. An increase in PTL thickness from 100 μm to 300 μm at a voltage of 1.625 V results in a decrease in current density from 0.736 A/cm2 to 0.722 A/cm2. Considering the influence of membrane thickness, improved cell performance is achieved with the thinner membrane. The current density increases by 73.25 % when the membrane thickness is reduced from 100 μm to 25 μm at an operating voltage of 1.60 V. Numerical results indicate a peak power density of 2.658 W/cm2 achieved at an operating voltage of 1.725 V and a temperature of 353.15 K. This study presents a novel approach by developing a fully coupled 3D CFD model that simultaneously considers electrochemical reactions, thermal transport, and structural parameters, including the thicknesses of the membrane and the PTL. This integrated framework allows for more accurate performance predictions than conventional models that overlook these necessary couplings. These results provide a basis for further development to improve the operation and design of PEMEL systems in real-world applications.